Towards An Innovative Generation: Increasing The Level Of Creative Thinking Skills In Science Learning In Elementary School With The RADEC Model - Khansa, Nur Aqila; Utama, Candra (Universitas Negeri Malang, 2024)
Learning science in elementary school requires an approach that encourages students' creative thinking skills. One model that can be used is the RADEC (Read, Ask, Discuss, Explain, Create) learning model. This model provides a systematic framework to develop students' creative thinking skills through a series of structured steps. In the RADEC learning model, students are asked to read the subject matter, ask challenging questions, discuss with classmates to share ideas and viewpoints, conduct experiments or direct observations, and create new solutions or products based on their understanding. Through this process, students not only understand science concepts deeply, but are also trained to think critically, analytically and creatively. By applying the RADEC learning model in science learning in elementary schools, it is expected to create an innovative generation that is able to face future challenges with strong creative thinking skills. This model provides a solid foundation for the development of students' creative potential and prepares them to become future leaders who are able to create new solutions in the world of science and technology.